Molecular Iodine Catalysed Benzylic sp3 C–H Bond Amination for the Synthesis of 2-Arylquinazolines from 2-Aminobenzaldehydes, 2-Aminobenzophenones and 2-Aminobenzyl Alcohols - Deshmukh, Dewal S.; Bhanage, Bhalchandra M. (Synlett, 2018)
Molecular iodine catalysed benzylic sp3 C–H bond amination has been developed for the synthesis of quinazolines from 2-aminobenzaldehydes and 2-aminobenzophenones with benzylamines. The use of oxygen as a green oxidant combined with the transition-metal-, additive- and solvent-free conditions makes the methodology economical and greener. The lack of aqueous work up also enhances the efficiency of this protocol. A series of 2-arylquinazolines was synthesised in good to excellent yields by using the developed protocol. 2-Aminobenzyl alcohols could also be employed to prepare the corresponding quinazoline derivatives.
Keywords: transition-metal free; benzylic sp3 amination; 2-arylquinazoline; molecular iodine; oxygen